From the shallows to the depths: a new probe set to target ultraconserved elements for Decapoda and other Malacostraca - Geburzi, Jonas C.; Rodríguez-Flores, Paula C.; Derkarabetian, Shahan; Giribet, Gonzalo (Frontiers in Marine Science, 2024)
Since its introduction about a decade ago, target enrichment sequencing of ultraconserved elements (UCEs) has proven to be an invaluable tool for studies across evolutionary scales, and thus employed from population genetics, to historical biogeography as well as deep-time phylogenetics. UCE probe sets are available for an increasing range of major taxonomic groups, including cnidarians, vertebrates, terrestrial arthropods, and mollusks. Here, we present the first probe set targeting UCEs in crustaceans, specifically designed for decapods and tested beyond decapods in other malacostracan lineages. Probes were designed using published genomes of nine decapod and one peracarid species, as well as raw Nanopore long reads of one additional brachyuran species. The final probe set consists of about 20,000 probes, targeting 1,384 unique UCE loci. We compiled a dataset across Malacostraca, as well as datasets of a deep-sea squat lobster genus, and an intertidal mangrove crab species, to test the probe set at different phylogenetic levels (i.e., class, order, genus, within species). Final mean UCE recovery from fresh samples across Malacostraca was 568 loci, with up to 847 and 658 loci recovered from decapod and non-decapod species, respectively. Final mean recovery from fresh samples in the genus-and within species-level datasets was 849 and 787 loci, respectively. Additionally, we recovered up to several hundreds of UCEs from historical museum specimens (10 to > 150 years old), that were included in all datasets, demonstrating once more that UCEs are a promising technique for leveraging museum specimens for genomic studies. Overall, our results highlight the versatility of this UCE probe set and its high potential for crustacean evolutionary studies.